PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN KETERAMPILAN MAKRAME SISWA KELAS V SD NEGERI 145 PEKANBARU - David Hendra Kurniawan Hendra Kurniawan; Zariul Antosa Zariul Antosa; Jesi Alexander Alim Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Base of problem in this research is the value of the students still under KKM. It is unknown, because the teacher does not involve students in the learning process, the teacher does not use the media during the learning process to take place, many students who are less interested in the teaching-learning process because it is considered less interesting, and presence of dependent students to other students who are superior,It is necessary for the improvement of learning with immediate application of learning models. Direct instructional model is a learning process that is more centered on the teacher (teacher centered), the teacher becomes the main information source and giver. Although the direct instruction method is used in addition to lectures and equipped or supported with the use of the media, the emphasis remains on the admissions process knowledge (subject matter) rather than on the search process and the construction of knowledge, and tend to emphasize the delivery of information sourced from textbooks, reference or personal experience. The study is in the form of classroom action research (PTK). This study aims to improve the skills makrame Elementary School fifth grade students 145 Pekanbaru. After the adoption of direct learning model can be applied, the data obtained from quantitative data. With the formulation of the problem is